EFEKTIVITAS PEMBENTUKAN UNIT PENGADUAN PELAYANAN PUBLIK (STUDI DESKRIPTIF PADA RUMAH SAKIT ANUTAPURA PALU) - Fajarwati, Indah (Katalogis, 2017)
This study was to find out how the implementation of the public service complaints unit at Anutapura General Hospital Palu and what constraints existing in that public service complaints unit. The types of data used in this study were primary and secondary data. The data collection was done by means of observations, interviews, documentations and triangulations. Informants were determined by using purposive sampling technique. The data analysis technique used in this study was qualitative data analysis model. The theory used was Campbell theory, consisting of 5 (five) aspects: program success, targeting success, satisfaction with program, input and output level, and comprehensive achievement to the goals. Based on the results of research conducted, it could be concluded that the effectiveness of the public service complaints unit establishment had not been maximal. First: the success of the public service complaints unit establishment at Anutapura General Hospital Palu was marked by the increasing number of complaints received, but there were some obstacles faced by the management of the complaints unit. Second; the targeting success of the public complaints unit establishment was marked by the increasing number of people complaints from various circles on public services that were not considered to be in accordance with the standards. However, there were still many complaints received repeatedly. Third: satisfactions with the public service complaints unit establishment were good because the complaints unit had been running in accordance with the standard operating procedures so that the complaints unit functioned effectively but still needed more good understandings from the Hospital officers. Fourth: the input and output level had been reached because the complaints were followed by quick follow-up complaints resolutions, but there were still many officers of the Hospital who did not understand the purposes of the complaints unit. Fifth: comprehensive achievement to the goals of the entire process above was materialized in accordance with the goals of the public service complaints unit improving the quality of service.